IDENTIFIKASI KAWASAN PERMUKIMAN KUMUH PERKOTAAN KELURAHAN FITU KECAMATAN TERNATE SELATAN KOTA TERNATE PROVINSI MALUKU UTARA - -, Indrajaya (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2020)
The purpose of this study was to determine the typology and level of slums of urban slums in Fitu Urban Village, South Ternate District, Ternate City, North Maluku Province. The research method used is the weighting and qounten analysis through qualitative and quantitative approaches both primary data and secondary data which are further described in the form of sentences in accordance with the subject matter studied. The results of the analysis show that the typology of urban slum areas Fitu Urban Village, South Ternate District, Ternate City, North Maluku Province is slum areas located in areas prone to natural disasters (volcanoes) and is categorized as heavy slums which requires comprehensive and sustainable handling and control